Outcome of patients aged 60‐75 years with newly diagnosed secondary acute myeloid leukemia: A single‐institution experience. (7th June 2019) - Bertoli, Sarah; Tavitian, Suzanne; Bories, Pierre; Luquet, Isabelle; Delabesse, Eric; Comont, Thibault; Sarry, Audrey; Huguet, Françoise; Bérard, Emilie; Récher, Christian
Abstract: A recent phase 3 trial showed that outcome of older patients with secondary acute myeloid leukemia (AML) may be improved by a liposomal encapsulation of cytarabine and daunorubicin (CPX‐351). This phase 3 study represents a unique example of prospective data in this rare subgroup providing basis for comparison with real life data. Here, we retrospectively assessed characteristics and outcome of patients aged 60‐75 years with secondary or therapy‐related AML in real life. Out of 218 patients that fulfilled CPX‐351 study criteria, 181 patients (83.0%) received antileukemic treatment either intensive chemotherapy (n = 121) or hypomethylating agents (HMA, n = 60). As compared with patients treated by chemotherapy, HMA‐treated patients were older, had lower WBC, more often AML with antecedent myelodysplastic syndrome and adverse cytogenetic risk. In chemotherapy‐treated patients, the complete response rate was 69%, median overall survival (OS) was 11 months whereas 3‐year and 5‐year OS was 21% and 17%, respectively. In HMA‐treated patients, the complete response rate was 15%, median OS was 11 months whereas 3‐year and 5‐year OS was 15% and 2%, respectively. In conclusion, although outcome of older patients with high‐risk AML is very poor, a significant proportion of patients treated by standard intensive chemotherapy but not HMA are long‐term survivors. Abstract : A recent phase 3 trial showed that outcome of older patients with secondary AML may be improved by CPX‐351. Here, we assessed characteristics and outcome of patients aged 60‐75 years with secondary or therapy‐related AML in real life. In chemotherapy‐treated patients, the complete response rate was 69%, median OS was 11 months whereas 3‐year and 5‐year OS was 21% and 17%, respectively. These results compared favorably with the control arm of the CPX‐351 trial.